Effects of dietary nucleotide and yeast extract supplementation on survival, growth, and post-metamorphic spinal deformities in Japanese eel Anguilla japonica from the leptocephalus to glass eel stage - Tadao Jinbo; Masato Higuchi; Takeshi Hano; Hirofumi Furuita; Kazuharu Nomura; Takashi Yatabe; Hiroshi Suzuki; Miyuki Mekuchi; Takashi Ishikawa; Youhei Fukui; Nobuto Kaneko; Yukinori Kazeto (Aquaculture Reports)
This study assessed the effects of dietary nucleotide (NT) and yeast extract supplementation on the survival, growth, and post-metamorphic spinal deformities of Japanese eel (Anguilla japonica) from leptocephalus to glass eel stages. Four dietary levels of a purified NT mixture of disodium salts containing equal amounts of inosine 5′-monophosphate (IMP), adenosine 5′-monophosphate (AMP), guanosine 5′-monophosphate (GMP), uridine 5′-monophosphate (UMP), and cytidine 5′-monophosphate (CMP) were added to the basal diet at increasing concentrations of 0.03 (D1), 0.49 (D2), 0.97 (D3), 1.92 (D4), and 3.76 % (D5) dry matter. Rearing trials were conducted from 6–80 days post-hatching (DPH) in experiment 1 and from 81–340 DPH in experiment 2. In experiment 3, D1 and D6 modified D1 by incorporating yeast extract with a high NT content at 3.39 % dry matter and used in the rearing trials from 81–321 DPH. In experiment 1, the survival rates of the NT-supplemented groups were significantly higher than that of the D1 group. Additionally, larvae in the D5 group at 20 and 60 DPH and larvae in the D3–5 groups at 40 DPH displayed significantly greater total lengths (TL) than those in the D1 group. The body depth (BD) to TL ratio in the D1 group was significantly higher than that in the other groups at 60 and 80 DPH. In experiment 2, there were no significant differences in growth; however, the survival rate demonstrated a similar trend to that of experiment 1 between the groups. Additionally, the proportion of severe spinal abnormalities in metamorphosed glass eels reduced with increasing NT content in the diets compared with that in the D1 group. Global metabolite analysis revealed that some nucleic acids and their relatives were present to a significantly greater degree in the muscle of leptocephali in the D5 group than those in the D1 group. In experiment 3, there were no significant differences in the survival rate, whereas the BD-to-TL ratio in the D1 group was significantly higher than that in the D6 group. Additionally, the proportion of severe spinal abnormalities in metamorphosed glass eels was significantly reduced in the D6 group compared to that in the D1 group. These results indicate that NT supplementation is essential for enhancing the health and quality of eel larvae and is a crucial strategy for sustainable aquaculture practices.